Primary cardiac lymphomas may present under different phenotypes. (March 2020) - Sromicki, Juri; Rodriguez, Hector; Reser, Diana; Van Hemelrijck, Mathias; Maisano, Francesco; Mestres, Carlos-A
Primary cardiac neoplasms are uncommon and often present with nonspecific cardiac symptoms. Proper treatment can only be initiated after histological analysis of a surgical specimen. Two cases of primary cardiac lymphoma with various clinical presentations and different growth patterns are presented here.